2009
DOI: 10.1038/cr.2009.32
|View full text |Cite
|
Sign up to set email alerts
|

Novel function of perforin in negatively regulating CD4+ T cell activation by affecting calcium signaling

Abstract: Perforin is a pore-forming protein engaged mainly in mediating target T cell death and is employed by cytotoxic T lymphocytes (CTLs) and natural killer cells. However, whether it also plays a role in conventional CD4 + T cell function remains unclear. Here we report that in perforin-deficient (PKO) mice, CD4 + T cells are hyperproliferative in response to T cell receptor (TCR) stimulation. This feature of hyperproliferation is accompanied by the enhancement both in cell division and in IL-2 secretion. It seems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…Apart from this, we found repulsive guidance molecule, which inhibits leucocyte migration and reduces inflammation (Demicheva et al 2015). In contrast, perforin can negatively regulate CD4 + T-cell activation and immune response (Bi et al 2009). In addition, alpha-1-acid glycoprotein 1 (Dalin 2015), histone-lysine N-methyltransferase (Yamashita et al 2006) and chitinase-3-like protein 1 (Kamba et al 2013) have also been reported to take part in inflammation.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Apart from this, we found repulsive guidance molecule, which inhibits leucocyte migration and reduces inflammation (Demicheva et al 2015). In contrast, perforin can negatively regulate CD4 + T-cell activation and immune response (Bi et al 2009). In addition, alpha-1-acid glycoprotein 1 (Dalin 2015), histone-lysine N-methyltransferase (Yamashita et al 2006) and chitinase-3-like protein 1 (Kamba et al 2013) have also been reported to take part in inflammation.…”
Section: Discussionmentioning
confidence: 80%
“…Immunoregulation and autoimmunity play an important role in the pathogenesis of uveitis. In contrast, perforin can negatively regulate CD4 + T-cell activation and immune response (Bi et al 2009). Monoclonal antibody blockade ICAM-2 causes the recruitment of inflammatory cells in the anterior chamber of eye during Pseudomonas aeruginosa infection (Hobden 2003).…”
Section: Discussionmentioning
confidence: 99%